Cervical Conization for Cervical Intraepithelial Neoplasia (CIN) 2 and 3 in HIV-Positive Women. Issue 2 (April 2015) - Babkina, Natalia; Heller, Debra S.; Goldsmith, Laura T.; Houck, Karen L.
<x xml:space="preserve">Abstract</x> Objective The purposes of the study were to investigate the outcomes of cervical conization for cervical intraepithelial neoplasia (CIN) 2 and 3 in HIV-positive women and age-matched HIV-negative controls and to determine whether positive margin, positive endocervical curettage, CD4 count, or viral load was associated with the persistence of CIN 2, 3 or residual CIN 2, 3 on the specimen from repeat excision procedure or hysterectomy. Materials and Methods HIV-positive women and HIV-negative controls with CIN 2, 3 on cervical conization were enrolled in the study. Patients who underwent repeat conization or hysterectomy were identified, and the specimens were evaluated for residual CIN 2, 3. CD4 count and viral load within 8 weeks of procedure were analyzed. Results A total of 44 patients and 44 age-matched controls were identified. Persistent CIN 2, 3 was diagnosed in 28 HIV-positive (63.6%) and 14 HIV-negative patients (31.8%; odds ratio [OR] = 4.7, 95% confidence interval [CI] = 1.9–11.5, p < .001). In HIV-positive women, a positive margin was associated with a higher persistence rate after cervical conization (OR = 5.3, 95% CI = 1.17–24.14, p = .03). In HIV-negative patients, positive endocervical curettage was associated with a higher persistence rate after conization (OR = 12, 95% CI = 2.24–64.23, p = .004). Of HIV-positive women, 75% had residual CIN 2, 3 on the specimen from repeat procedure compared to 45.2% of controls (OR = 3.6, 95% CI = 1.3–10.6, p = .018). CD4 count or viral load was not associated with the rate of residual disease or persistence rate after cervical conization, but the lowest OR that the sample size allowed to assess with 90% power was 5.02. Conclusions HIV-positive women have a higher rate of residual disease and higher persistence rate after conization for CIN 2, 3 than age-matched HIV-negative controls.